Cobalt and Copper Recovery from the Ancient Flotation Tailings using Selective Sulfation Roast - Leaching Process (Journal of Mining and Metallurgy, Section B: Metallurgy, 2019)
The ancient flotation tailings from Lefke, Cyprus, have a potential for non-ferrous metals such as cobalt and copper from more than 9.5 million tons of reserves containing 0.38% Cu, 0.032% Co, and 22.6% Fe. Recovery of cobalt and copper from these tailings would provide great benefits from economic and environmental perspectives. Therefore, in this study, following determination of the mineralogy and chemical composition of the tailings, certain processes such as direct leaching and sulfation roasting with/without additives before leaching were applied. Since low metal extractions were obtained from direct leaching, a selective sulfation process was applied on the tailings before leaching in order to produce a pregnant solution containing higher amounts of Co and Cu metals by reducing the iron concentration. When sulfation roasting was performed without any additive, the desired selectivity could not be provided, since the sample was considerably oxidized under atmospheric conditions in the past. Therefore, the usage of Na2SO4 as an additive with the amount of 25% at a roasting temperature of 700ºC was tested. Consequently, the Na2SO4 improved the sulfation and resulted in higher cobalt (90.1%) and copper (71.2%) recovery in leaching. Beside this, an improvement with a selective sulfation was obtained by the promoting effect of Na2SO4 and the iron extraction decreased from 26.1% to 3.9%.